MANAGING AUDIT CHALLENGES IN THE ERA OF BIG DATA: AN IN-DEPTH REVIEW - Richardson, Michael (International Journal of Contemporary Research in Marketing and Management Sciences, 2024)
As the influence of big data technology continues to proliferate, numerous industries experience its transformative effects. Among them, corporate audit, a vital tool for ensuring the veracity of financial data, is undergoing significant changes and challenges within this evolving landscape. The substantial volume of data, intricate data structures, and emerging data analysis techniques ushered in by big data present unprecedented opportunities for the field of auditing. However, they also introduce substantial risks. Consequently, comprehending these risks deeply and proactively addressing them is now a central focus in modern auditing research. This task encompasses not only the practical execution of auditing but also the conceptual and methodological innovation and advancement in the auditing domain